IMPACT OF HURRICANE IRMA ON EVACUATION PREPAREDNESS AND RESPONSE OF FLORIDA ASSISTED LIVING COMMUNITIES. (11th November 2018) - June, J; Peterson, L; Dosa, D; Thomas, K; Li, M; Sun, X; Sakib, N; Hyer, K
Abstract: Hurricane Irma threatened Florida in September 2017, making landfall first in Key West then in Southwest Florida. State regulations require assisted living communities (ALs) to have a comprehensive emergency plan (CEMP) that includes procedures to shelter in place or evacuate. Further, they must update their evacuation status through FLHealthSTAT, an online monitoring system. After Hurricane Irma, the Florida Agency for Health Care Administration (AHCA) performed the Hurricane Irma Impact Survey (HII) to determine experiences of ALs and other care facilities. Information gathered included when and where the AL evacuated, how many residents evacuated with family, if they followed their CEMP, if they required help from emergency management to evacuate, and if they lost power. The current study compared the evacuation status of Florida ALs and the experiences of those that evacuated. Chi-square and t-tests were performed to determine significant characteristics. Data includes 2, 309 ALs that had registered in FLHealthSTAT and responded to the HII survey. Results indicate 439 (14.5%) of Florida ALs evacuated. Those with a Limited Mental Health license were less likely to evacuate (p=.004). Also, those that did evacuate had a lower proportion of Optional State Supplement beds, for low-income residents (p<.001). Results also indicate that evacuated ALs were not able to follow their CEMP, citing issues with the evacuation site and transportation. This study is an important insight into the monitoring and experiences of ALs during evacuations. This and further studies can help researchers and policymakers learn more about aiding ALs during disasters.